2007
DOI: 10.1007/s10067-007-0582-5
|View full text |Cite
|
Sign up to set email alerts
|

Palmar fasciitis and polyarthritis syndrome associated with non-small-cell lung carcinoma

Abstract: A 56-year-old man presented with pain and stiffness in both shoulders and developed severe, rapidly progressive contractures of the fingers. Examination revealed subcutaneous thickening in both palms with fixed flexion deformities of all digits except the thumbs. Initial investigations including a malignancy screen were all normal/negative. Eighteen months later, he was diagnosed with metastatic non-small-cell lung carcinoma. Although rare, palmar fasciitis and polyarthritis syndrome is an important paraneopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The process can be at least halted by successful treatment of the malignancy, although the contractures and functional difficulties seem to persist. [13][14][15]17,21,24,28,37 Glucocorticoids and other drugs to modify the process have not been successful in previous cases or in this case.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The process can be at least halted by successful treatment of the malignancy, although the contractures and functional difficulties seem to persist. [13][14][15]17,21,24,28,37 Glucocorticoids and other drugs to modify the process have not been successful in previous cases or in this case.…”
Section: Discussionmentioning
confidence: 86%
“…* Bone scans, when reported, have (as in this case) shown uptake consistent with degenerative change. 37,38 But others have reported more definite inflammatory uptake, 4,30,31,34,39 demonstrating the variability in the degree of articular involvement in this condition. Inflammatory markers are typically not raised, and autoantibody screening is usually negative.…”
Section: Discussionmentioning
confidence: 96%
“…We performed a Medline literature search (1950-present) using the keywords paraneoplastic syndrome, rheumatoid arthritis, arthritis, paraneoplastic polyarthritis, malignancy and cancer to review all reported cases of paraneoplastic arthritis. Several case reports discuss this arthritis in association with various cancers (Table 1) [2][3][4][5][6][7][8][9][10][11]. It is also discussed in the literature how recognition of the polyarthritis and other paraneoplastic syndromes may assist in the early detection of some of these malignancies [12].…”
Section: Discussionmentioning
confidence: 97%
“…9 It is reported that if the ovarian carcinoma remits the PFPA symptoms abate, although contractures may remain. 13 The relentless course of the indurated palmar erythema in the presence of progressive polyarthritis was an indicator for a paraneoplastic presentation of PFPA in our patient and prompted oncological review.…”
Section: Discussionmentioning
confidence: 98%